1995
DOI: 10.2135/cropsci1995.0011183x003500050010x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Related Wheat Stocks Possesing 1B or T1BL·1RS Schromosomes: Grain and Flour Quality

Abstract: The agronomic advantage of the T1BL. 1RS translocation and the potential importance of chromosome 1BS to end‐use quality of bread wheat (Triticum aestivum L.) warrant a more precise definition of the relationship of T1BL‐1RS to bread wheat quality. This study was conducted to determine the effect of TIBL. 1RS from ‘Aurora’ on grain and flour quality in multiple near‐isoline pairs with varying genetic background, and to examine the genetic variation among random inbred lines selected only for 1B or T1BL 1RS. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Basis of genetic diversity among 1BL.1RS translocations Various effects of wheat genetic background and rye sources have been addressed as major factors in inconsistent agronomic performance and end-use quality traits of 1BL.1RS translocations (Singh et al 1998;Villareal et al 1991;Carver and Rayburn 1995;McKendry et al 2001McKendry et al , 1996Kumlay et al 2003;Kim et al 2004Kim et al , 2005. In those studies either near-isogenic lines or recombinant inbred lines were used in trials, in which the residual confounding impact of impure genetic background of wheat could not be separated from the effects of the introgressed rye chromosome arm.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Basis of genetic diversity among 1BL.1RS translocations Various effects of wheat genetic background and rye sources have been addressed as major factors in inconsistent agronomic performance and end-use quality traits of 1BL.1RS translocations (Singh et al 1998;Villareal et al 1991;Carver and Rayburn 1995;McKendry et al 2001McKendry et al , 1996Kumlay et al 2003;Kim et al 2004Kim et al , 2005. In those studies either near-isogenic lines or recombinant inbred lines were used in trials, in which the residual confounding impact of impure genetic background of wheat could not be separated from the effects of the introgressed rye chromosome arm.…”
Section: Discussionmentioning
confidence: 99%
“…Sec-1 was identified by acid polyacrylamide gel electrophoresis (A-PAGE, pH 3.2) using the protocol described in Yan et al (2005). Evaluations of grain and flour quality followed procedures described in detail by Carver and Rayburn (1995); Martín et al (2001), and Kumlay et al (2003), with modifications of Yan and Ren (2004). *Disease severities are on an infection type scale of 0-9 (Leath and Heun 1990; Wan et al 2004) where, 0 = immune, no visible symptoms; 1-3 = resistant, increasing from (i) flecks, no necrosis to (ii) necrosis, to (iii) chlorotic areas with slight sporulation; 4-6 = intermediate, chlorotic areas decreasing in amount while mycelium and conidial production increases from slight to moderate; 7-9 = susceptible, increasing amount, size, and density of mycelium and conidia to a fully compatible reaction…”
Section: Resistance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…There is little information on the role of carbohydrate components in the swelling process. CARVER and RAYBURN (1995) reported that starch-gluten interaction infl uences SDS sediment, and according to MAGHIRANG and co-workers (2006) it can possibly be affected by pentosans or damaged starch as well. Therefore, we fi nd it necessary to consider the role of carbohydrate composition in the sedimentation measurements, especially when unusual carbohydrate components, like dietary fi bre compounds, are present in considerable amounts.…”
mentioning
confidence: 94%
“…This chromosome arm carries resistance genes against different rust species and powdery mildew (Lr26, Sr31, Yr9, Pm8) (McIntosh 1988). Moreover, several studies have suggested that it enhances the yield potential of wheat in certain genetic backgrounds (Carver and Rayburn 1995;Moreno-Sevilla et al 1995;Villareal et al 1995Villareal et al , 1998. One major concern about this translocation is its single origin (Schlegel and Korzun 1997), with the consequence being the absence of any allelic variation on this chromosome arm.…”
Section: Introductionmentioning
confidence: 99%